Prevention of HIV/AIDS in Indonesian Navy views of Knowledge, Attitude, and Practice - Arwinda Yuhan Wirahayu; Prijono Satyabakti (Universitas Airlangga, 2014)
HIV/AIDS is a disease that is spreading rapidly in many countries, including in Indonesia. This study to identify the prevention of HIV/AIDS views of knowledge, attitudes and practice. The methods used in this research was descriptive observational with the entire population in Indonesian Navy at east area of Satuan Kapal Eskorta Komando Armada RI Kawasan Timur. Sample size was 87 respondents were selected by purposive sampling technique. Variables in this research are respondent characteristics (age, education, marital status, years of work, mobility), and the prevention of HIV/AIDS from their knowledge, attitude, and practice. The results showed that the characteristics of the respondents most of comprised of age group 20–26 years (54.02%). Most respondents were graduate from high school (87.36%). Most respondents were single (52.87%). Most of respondents were working > 5 years (52.87%) and most of respondents mobility > 5 months (41%). The result of prevention HIV/AIDS showed most of respondents knowledge about HIV/AIDS were in good category (60.91%), most of respondents attitudes about HIV/AIDS were in good category (72.41%). And most of respondents practice about HIV/AIDS were in good category (93.10%). It could be conclude that prevention of HIV/AIDS on Indonesian Navy east area of Satuan Kapal Eskorta Komando Armada RI Kawasan Timur are seen from their knowledge, attitudes and practice are in good category.